(untitled) (Al-Academy, 2023)
In light of the intellectual and technological progress within the current developments of time, as well as the emergence of digital tools and means of display and communication, which had a major role in the shifts of the time of globalization in various commercial and economic fields, as well as areas of transferring the design image and its stages of development to customers and the convergence of views between the customer and the interior designer, which are the most important pillars of the design process As a whole, and accordingly, there is an urgent need for a process of intellectual balance between them through digital tools from the technical side and through social media from the intellectual side. Customer comments via social media, which facilitates the process of generating feedback for designers. The problem is embodied in the following question: "How can digital modeling tools and social media be employed in the field of interior design to obtain a contemporary design process?" And then its objectives, limits, and definition of its terminology, as the research sample was represented by the engineering offices registered with the Iraqi Engineers Association, and after reviewing previous studies and building the theoretical framework, the research dealt with two axes, the first (the concept of the design process and its variables’ connection with the variables of the era and technology), and the second (the role of the customers’ position in the process After building the theoretical framework and reaching a set of indicators, a questionnaire was built to be analyzed in the light of it, and after ensuring the validity and reliability of the tool, a random sample was selected from the number of answers obtained from the research community, and the statistical analysis method was used For the questionnaire, a set of statistical results were reached in order to influence a set of conclusions that can be generalized to the research community, and then a set of recommendations and research proposals.